And when one does not want to fight and the other does? Considerations about judicialization affective relationships in the city of Vila Velha/ES - Oliveira, Magali Gláucia Fávaro; Santos, André Filipe Pereira Reid dos (FCL-UNESP Laboratório Editorial, 2014)
This article aims to investigate the legitimacy of the justiciability of affective relationships resulting from the physical and psychological violence perpetrated against women in the home and family environment. To this end, data collection was conducted in a Specialized Court on domestic violence against women in the city of Vila Velha / ES, which comprised 144 applications for injunctions distributed to stick in the months from April to June 2011. The data revealed that male supremacy is a deeply established social constant that emerges from a state of exclusion of women, generating natural aggressions perpetrated in the domestic sphere. However, it is noted that there is already small and major changes in the social picture of Brazilian women and that the Maria da Penha Law has played an important role in this fight.